ROBOT PENCARI BENDA MENGGUNAKAN PERINTAH SUARA BERBASIS ARDUINO UNO - Ilamsyah Ilamsyah; Hendri Iksan Setyawan; Alfianti Syahfitri (UNIVERSITAS RAHARJA, 2017)
The progress of the computerized field is generally high in the field of microcontrollers are increasingly increasing especially in the community. This study aims to determine the feasibility of a technology by using media robot search objects that are useful for the community. Thisresearch uses development research approach and continued with research of observation action. This research uses RGB color filtering method where a sensor chooses according to the color you want to search and activate sound to move a robot. Data processing research conducted by descriptive quantitative. In the field of computers that have a very important role in the world of information technology and serves as a medium that can process creativity, and imagination into a real form, then designed an object-finding robot using arduino uno-based voice command that has the intelligence to help people forget to put a object. Using available sensors, ie light-colored sensors to detect objects, use ultrasonic sensors to avoid robotic collisions with objects. Equipped with a desktop application to display the distance of a specified object with a wheel spin scale. Connect using bluetooth. As a robot to help humans in terms of finding an object. For the construction of robots using multiple motors and sensors. But the processing power, memory, and communication capabilities are not much different from other robots that use PDA or laptop devices. This robot system uses ARM voice in control using a smartphone, so the robot is more effective to use, and useful to help the job.